Assessment of the satisfaction of partners on site-specific fertilizer recommendations in selected districts of Ethiopia - Adimassu, Zenebe; Ebrahim, Mohammed; Tibebe, Degefie; Tamene, Lulseged D.; Abera, Wuletawu; Tilaye, Asmalu; Mesfine, Tewodros; Liben, Feyera; Gashaw, Getachew; Tesfu, Daniel; Endrias, Abrham (2023)
The study on satisfaction of experts and farmers with the advisory service on Site-Specific Fertilizer Recommendations (SSFRs) and climate information services (CIS) was conducted to assess the level of satisfaction of these partners with the various training, SSFRs advice, and climate forecast information services. Primary data were collected from 27 experts and 202 farm households from 10 districts in the Amhara, Oromia, and SNNP regions. All of the experts and 95.5% of the farmers received training on SSFR. However, only 78% of the experts and 60% of the farmers received training on CIS. The assessment showed that out of those who received training, more than 80% of experts and farmers were satisfied with the content, methodology, appropriateness, and time allocated to SSFRs training. Similarly, a significant proportion of the experts (>80%) were satisfied with the various aspects of training on CIS. However, farmers were not as such satisfied with the training approach and time allocation on CIS training. This implies that the training approach and time allocation for CIS should be improved for the future. Overall, the study also showed that more than 95% of the farmers were satisfied with various attributes of SSFR including fertilizer rate, time of application, and yield advantage over the conventional fertilizer recommendation. The result of this assessment suggests that there is a need to scale out the various trainings and training and LSFR to agro-ecologies and crop types.